2011
DOI: 10.1021/la2000624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Constraint on Crack Pattern Formation in Thin Films of Colloidal Polystyrene Particles

Abstract: Crack formation and the evolution of stress in drying films of colloidal particles were studied using optical microscopy and a modified cantilever deflection technique, respectively. Drying experiments were performed using polystyrene particles with diameters of 47 ± 10 nm, 100 ± 16 nm, and 274 ± 44 nm that were suspended in water. As the films dried, cracks with a well-defined spacing were observed to form. The crack spacing was found to be independent of the particle size used, but to increase with the film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 27 publications
3
74
0
Order By: Relevance
“…Also, the mechanisms that control the resistance to fracture of the wet particulate body are not known. The study of the spacing between cracks has also been a recent interest …”
Section: Drying and Crackingmentioning
confidence: 99%
“…Also, the mechanisms that control the resistance to fracture of the wet particulate body are not known. The study of the spacing between cracks has also been a recent interest …”
Section: Drying and Crackingmentioning
confidence: 99%
“…26,27 The crack formation mechanism is a complex function of several parameters such as particle size, 28 charge, 29 shear modulus, 30 and process parameters such as evaporation rate. 31 The manipulation of substrate properties 32 to control the crack formation process has recently gained importance. The aim is to have higher critical cracking thicknesses, and several studies report innovative approaches to achieve the same.…”
Section: Introductionmentioning
confidence: 99%
“…A little further behind the compaction front, the film is observed to form cracks that propagate parallel to the drying direction. These cracks form as a result of stresses that build up in the film due to substrate constraints, which confine the drying film and leave it in a state of tension89. Dufresne et al 17 observed similar cracks to the ones shown in Fig.…”
mentioning
confidence: 81%
“…The complexity of the drying process and the stress distributions that build up in these coatings have meant that providing an accurate theoretical description of the failure mechanisms in colloidal nanoparticle films has been challenging. However, a number of authors have studied how factors such as film thickness23, particle size45, drying rates67 and substrate constraints89 influence the failure mechanisms in thin nanoparticle films. Delamination is one such failure mechanism which can undermine the physical stability of a coating and occurs when a film debonds from its substrate.…”
mentioning
confidence: 99%